Parent's report on oral health-related quality of life of children with cystic fibrosis - PEKER, MEHMET SERTAÇ; GÖKDEMİR, YASEMİN; ERDEM ERALP, ELA; KARADAĞ, BÜLENT TANER; KARGÜL, BETÜL (My University, 2022)
Background Health-related quality of life (HRQoL) scales are now widely used in children with cystic fibrosis (cwCF) which reflects the course of the disease. In this cross-sectional study, our primary aim was to compare the Pediatric Oral Health-Related Quality of Life (POQL) and Oral Health Score (OHS) between cwCF and healthy group. Our secondary aim was to evaluate the association between Pseudomonas aeruginosa (PA) colonization, pulmonary function test, OHS and POQL in cwCF. Methods The study population (age ranging 6-14) included 55 cwCF followed at the Marmara University Division of Pediatric Pulmonology compared with 50 healthy peers. A survey consisted of general questions (age, sex, etc.) and the POQL instrument were filled by parents. The decayed, missing, and filled teeth for both primary (dft) and permanent dentition (DMFT) was detected according to WHO criteria. Data like current body mass index (BMI z score), colonization status with PA, predicted value for forced expiratory volume in 1 second (FEV1pp), and any hospitalizations during the previous year were obtained from their medical. Differences between the groups were evaluated using Chi-square and Mann-Whitney U test with a significance level set at 0.05. Results There was no significant difference between PA-colonized cwCF and healthy controls in DMFT (p = 0.916). For all domains of POQL (emotional function, social function, role function), scores of cwCF were significantly better than healthy controls (p 0.05). Conclusion Although POQL scores of cwCF were encouraging, dental caries prevention and regular follow-ups should be taken into consideration.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; Solunum Bakımı; Pediatri; Akciğer ve Solunum Tıbbı; Pediatri, Perinatoloji ve Çocuk Sağlığı; Respiratory Care; Pediatrics; Pulmonary and Respiratory Medicine; Pediatrics, Perinatology and Child Health; cystic fibrosis (CF); oral health; pediatric dentistry; Pseudomonas aeruginosa (PA); quality of life; DENTAL-CARIES; cystic fibrosis (CF); oral health; pediatric dentistry; Pseudomonas aeruginosa (PA); quality of life